Effect of dietary supplementation of Lawsonia inermis and Acacia nilotica extract on growth performance, intestinal histopathology, and antioxidant status of broiler chickens challenged with coccidiosis - Fares A. Eldeeb; Enas A. Noseer; Shimaa Abdelazeem; Esraa Ali; Asmaa W. Basher; M. A. A. Abdalla; Hytham H. Ibrahim (BMC Veterinary Research)
Abstract Avian coccidiosis is one of the many disorders that seriously harm birds’ digestive systems. Nowadays the light is shed on using Phytochemical/herbal medicines as alternative natural anti-coccidial chemical-free standards. Consequently, this study aimed to investigate the impact of lawsonia inermis powder (LIP), and Acacia nilotica aqueous extract (ANAE), on growth performance, serum biochemical, antioxidant status, cytokine biomarkers, total oocyst count and intestinal histopathology of broiler chickens challenged with coccidiosis. Two hundred and forty-one-day-old Ross chicks were randomly distributed into 8 groups, four were challenged with coccidia, while the other four were unchallenged. Each group consisted of 3 replicates of 10 chicks each. The birds were challenged with Eimeria species orally on day 14 of age. Group 1B was unchallenged, and Group 2 A was challenged with coccidiosis and both were fed the basic diet without additives. Groups 3 A, 4 A, and 5 A were challenged and fed on the basic diet supplemented with LIP (40 g/kg of diet), ANAE (5 g/kg of diet), and LIP + ANAE combination, respectively. Groups 3B, 4B, and 5B were unchallenged and fed on the basic diet supplemented with LIP (40 g/kg of diet) and ANAE (5 g/kg of diet) and LIP + ANAE combination, respectively. The best results of growth performance parameters were recorded in G5B, and G5A followed by the group fed on ANAE and then the group fed on LIP compared with the control. All challenged broilers had higher aspartate aminotransferase (AST), alanine transaminase (ALT), urea, creatinine, glucose, MDA, IL-4 &TNF-α levels compared to all unchallenged broilers. Challenged broilers had lower serum cholesterol, triglycerides, total protein, albumin, globulin, SOD, GPX & IL-10 levels compared to non-challenged broilers. Histopathological examination of the small intestine and cecum of challenged treated groups with LIP + ANAE showed good mucosal integrity, few leukocytes infiltration, and low total oocyst count in broilers manure, followed by ANAE then LIP groups. In conclusion, dietary supplementation of lawsonia inermis powder and Acacia nilotica aqueous extract either alone or in combination had positive effects on broiler performance, blood metabolites, antioxidant status, cellular response, and intestinal morphology during the exposure to Eimeria spp. as a potential natural anti-coccidial.